2009
DOI: 10.1590/s1808-18512009000100008
|View full text |Cite
|
Sign up to set email alerts
|

Prótese para substituição total de disco intervertebral: desenvolvimento de modelo computacional e análise por elementos finitos

Abstract: INTRODUÇÃO: a idéia de um disco intervertebral artificial não é nova. O campo de estudos sobre próteses para artroplastia de coluna desenvolve-se ao passo que novas tecnologias na área de materiais e engenharia médica são desenvolvidas ou introduzidas para o surgimento de novos projetos. OBJETIVO: estabelecer metodologia de desenvolvimento de produto em um projeto de prótese para substituição total de disco intervertebral pela utilização de ferramentas computacionais de engenharia. MÉTODOS: a metodologia de de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It is known that the cyclical biomechanical efforts to be considered in orthopedic implant projects are very important. These efforts generate cyclic fatigue in the implanted materials, which is one of the most critical flaws observed in prostheses, causing the total replacement of the intervertebral disc (CAMPELLO et al, 2009). Therefore, biomechanical analysis and longitudinal clinical research are required in order to determine the influences and consequences of stress on implants and adjacent structures, as well as the anatomical and soft-tissue interferences that vary from animal to animal (BARBIER et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the cyclical biomechanical efforts to be considered in orthopedic implant projects are very important. These efforts generate cyclic fatigue in the implanted materials, which is one of the most critical flaws observed in prostheses, causing the total replacement of the intervertebral disc (CAMPELLO et al, 2009). Therefore, biomechanical analysis and longitudinal clinical research are required in order to determine the influences and consequences of stress on implants and adjacent structures, as well as the anatomical and soft-tissue interferences that vary from animal to animal (BARBIER et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The metal-metal contact exacerbated the stress on these points, increasing friction during extension, lateral bending, and flexion. Studies on cervical devices observed that the core of the prosthesis is the most stressed component during axial compression and compression/shear (MUMMANENI et al, 2007;CAMPELLO et al, 2009). The distribution of stresses on the cranial surface of the P2 vertical plate is also explained by the lack of a shock-absorber on the metal contact surfaces.…”
Section: Applied Forcementioning
confidence: 99%
“…Another limitation is that the contact was considered perfect in the FE analysis, but the coefficient of friction between the two parts of the prostheses was not considered. Knowledge of the behavior of biomedical devices under cyclic loads is fundamental because cyclic fatigue in the implanted materials is one of the most critical failures observed in cervical disc prosthesis (CAMPELLO et al, 2009). Therefore, additional biomechanical and long-term follow-up studies are needed to properly assess the biomechanics and safety of this type of device (BARBIER et al, 1998).…”
Section: Applied Forcementioning
confidence: 99%